Purification and Characterization of Lactoferrin from Camel Urine - Ahmad, K. A.; Jada, M. S.; Wurochekke, A. U. (African Journal of Biochemistry and Molecular Biology Research, 2025)
This study reports the isolation, purification, characterization, and antimicrobial activity of lactoferrin derived from camel urine. The lactoferrin was purified through a sequential process involving acetone precipitation, dialysis, ion exchange chromatography, and gel filtration. The partially purified protein was then characterized with respect to its molecular weight, pH and temperature optima, metal ion interaction, and thermal stability. The purification process achieved a 3.23-fold increase in purity with a specific activity of 6.33 U/mg protein and an overall yield of 9.74%. The purified lactoferrin exhibited a molecular weight of 75 kDa and demonstrated optimal activity at pH 7.0 and 40 °C in 50 mM sodium phosphate buffer. Among the metal ions tested, Zn²⁺ enhanced lactoferrin activity, while Mg²⁺ and Al³⁺ acted as strong inhibitors. These findings confirm the potential of camel urine as a novel and viable source of bioactive lactoferrin and lay the groundwork for further biotechnological exploration of its therapeutic applications.